Penggunaan Model Pembelajaran Inkuiri Terbimbing Dalam Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas III MI Al-Azhar Menganti Gresik - Barudin; Misbahul Jannah; Zulfatmi (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2023)
The purpose of this research is to find out the use of guided inquiry learning models in improving students' critical thinking skills. The design of this research is action research, because the research is conducted to solve learning problems in the classroom. This research also includes descriptive research, because it describes how a learning technique is applied and how the desired results can be achieved. the results of the research and discussion related to the application of the Guided Inquiry learning model to improve the critical thinking skills of students in class III B thematic learning at MI Al-Azhar Menganti Gresik in the 2022-2023 academic year, it can be concluded that the results of observing teacher activity in each cycle have changed and experienced an increase. This increase can be seen from several aspects, namely teacher activity, student activity, and students' critical thinking skills that have achieved predetermined performance indicators, namely ≥ 80% experiencing success.